THE PROBLEM OF RESPONSIBLE ATTITUDE STUDENTS BEFORE STUDYING - L.V. Beshevets (Academy of Cognitive and Natural Sciences, 2022)
The article is discovered content of concept "responsible concern to the studies", character o f levels its forming is defined, its initial level and causes o f low level of the forming at students of the pedagogical university is defined too.